Hyper-Ritualitas : antara Determinisme Teknologi dan Hindu Nusantara - Hari Harsananda (Sanjiwani: Jurnal Filsafat, 2021)
The world is entering the post-modern era with the Covid-19 pandemic has further strengthened the existence of technology in the world. Technological developments are increasingly advanced, penetrating other cultural elements, including the religious system. Technological determinism forms a “simulacra” that turns ritual into hyper-rituality. Rituals formed artificially through the internet network. Hindu Nusantara has a formulation in the form of Mantras, Mudra, Aksara, Mandala, Yantra and Kala which is a reason, that technological determinism that makes Hyperituality is actually a process of reducing the spiritual values ​​of a religious ritual.